Discrete Time Dynamic Model for Telescope Auto-Guiding System - Joon Hwa Lee (Journal of Astronomy and Space Sciences, 2007)
In the auto-guiding system for obtaining a long exposure astrophotography, CCD camera is usually used for measuring guide errors which are affected by optical dispersion and mechanical disturbances. In this paper, a discrete time dynamic model and a performance index are proposed for analysing the auto-guiding system. The optimal gain for proportional control is derived considering the optical dispersion and the disturbances. Some experiments are provided to illustrate that the optimal control gain is lower as the optical dispersion is higher.